Signaling Family Firm Identity Familiy Firm Identification and its Effects on Job Seekers' Perceptions about a Potential Employer - Wolf, Sandra (Familienunternehmen und KMU,, 2018)
Sandra Wolf develops a better understanding of the importance of clearly communicating family influence. She examines the efficacy of brand elements that signal family influence and that help external stakeholders to identify a family firm. An experiment with 543 students in Germany and Switzerland is carried out to empirically test the derived hypothesis. The results highlight two important findings. Firstly, the importance of a family firm tagline as well as the family name as brand elements are able to signal "family firm" and this helps potential employees to immediately categorize the potential employer. Secondly, a positive relationship between the identification of a family firm and applicant attraction was confirmed as to that the relationship is serially mediated by perceived brand authenticity and perceived benevolence. Contents Exploring the Effects of Brand Elements on Signaling and Identifying Family Firm Identity Family Firm Identity as a Signal to Influence Perceived Trustworthiness in Initial Recruitment Processes Target Groups Researchers and students in the fields of business adminstration, management, marketing and human resources Practitioners in the areas of management, marketing, human resources, corporate strategy The Author Dr. Sandra Wolf wrote her dissertation under the supervision of Prof. Dr. Andreas Hack at the Witten Institute for Family Business (WIFU) at Witten/Herdecke University.